KONSEP RUKSHAH DAN IMPLEMENTASINYA DALAM HUKUM PERNIKAHAN - Ahmad Jalili (STAIN Sultan Abdurrahman Kepulauan Riau, 2018)
This study will focus on answering the following problems: How does the concept of concession according to scholars of usul fiqh (ushuliyyûn)? How does the concept confirmed by maqashid sharia Islamic rulings? How to apply concession in marriage rulings? This research is a descriptive qualitative research that seeks to uncover the circumstances that are natural in a holistic manner. Problems and facts will be illustrated by description, then analyzed to obtain a complete picture of the issues to be studied. In accordance with the object of study, the research also included the type of library research. Urgency of usul fiqh research cannot be denied in the study of Islamic sciences. Therefore, it is important to continue this kind of research focusing on the implications of the study confirmed in the field of jurisprudence, particularly in fiqh jinayat and fiqh Muamalat.